2013
DOI: 10.1007/s00417-012-2256-5
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective evaluation of the effect of hydroxyquinine on RPE thickness

Abstract: Treatment with hydroxychloroquine was associated with increased thickness of the outer band of the retinal pigment epithelium layer. This finding may explain the protective effect of hydroxychloroquine against age-related macular degeneration (AMD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Mahon et al [ 24 ] reported an apparent accumulation of autophagic granules in cone photoreceptor cells exposed to chloroquine in an animal model. Pikkel et al [ 25 ] indicated increased thicknesses of the outer band of the retina in the macular area in patients who were treated with hydroxychloroquine, compared to the control subjects. They supposed that the thickening of the outer band observed in patients resulted from thickening of Bruch's membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Mahon et al [ 24 ] reported an apparent accumulation of autophagic granules in cone photoreceptor cells exposed to chloroquine in an animal model. Pikkel et al [ 25 ] indicated increased thicknesses of the outer band of the retina in the macular area in patients who were treated with hydroxychloroquine, compared to the control subjects. They supposed that the thickening of the outer band observed in patients resulted from thickening of Bruch's membrane.…”
Section: Discussionmentioning
confidence: 99%
“…It is used as an antimalarial drug ever since the Second World War. It is also widely used in the treatment of lupus erythematosus, rheumatoid arthritis, and other inflammatory and skin diseases [ 10 , 11 , 12 , 13 , 14 ]. Hydroxychloroquine is rapidly absorbed by the intestine, accumulating in organs such as the liver, spleen, lungs and kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have examined means of preventing the development of AMD. Some studies focused on the correlation of retinal thinning or thickness with the development and progression of non-exudative (dry) AMD [ 18 , 19 , 20 , 21 ]. Others focused on ocular manifestations in early AMD that are associated with the choroid [ 22 ].…”
Section: Discussionmentioning
confidence: 99%